Robustness on Intuitionistic Fuzzy Connectives - Reiser, Renata Hax Sander; Bedregal, Benjamin Callejas (Trends in Computational and Applied Mathematics, 2014)
<!--StartFragment-->The main contribution of this paper is concerned with the robustness of intuitionistic fuzzy connectives in fuzzy reasoning. Starting with an evaluation of the sensitivity in $n$-order functions on the class of intuitionistic fuzzy sets, we apply the results in the intuitionistic $(S,N)$-implication class. The paper formally states that the robustness preserves the projection functions in such class.